Preparation of anti rush paint with waste expanded polystyreme - Muhammad Salihin Zakaria
In this final year project, waste polystyrene foam is used as binder to develop a paint formulation in place of acrylic and vinyl binder in commercial paints which are derived from the products of refining crude oil. The principle target of the experimental program was to determine the optimum formulation in contributing the best performance of the paint development from polystyrene foam waste.